Kinetika Produksi Gas, Kecernaan Bahan Organik dan Produksi Gas Metana in Vitro pada Hay dan Jerami yang Disuplementasi Hijauan Mengandung Tanin - A Jayanegara; A Sofyan; H.P S Makkar; K Becker (Media Peternakan, 2009)
This research was aimed to evaluate supplementation of tannin-containing forages, namely Rhus typhina and Salix alba into hay and straw diets on rumen fermentation parameters in vitro, especially on methane production. Supplementation was applied at 30% dry matter replacement from hay and straw diets. Treatments consisted of: H (hay), J (straw), RT (R. typhina), SA (S. alba), H:RT (hay:R. typhina, 70:30), H:SA (hay:S. alba, 70:30), J:RT (straw:R. typhina, 70:30), and J:SA (straw:S. alba, 70:30). Incubation was applied using Hohenheim gas production method for 24 hours. Variables measured after incubation were cumulative and kinetics of gas production, methane emission and organic matter digestibility. The results showed that supplementation of R. typhina and S. alba decreased (P < 0.05) percentage of methane production by 11.2% and 4.3% when added to hay, respectively; while it decreased (P < 0,05) percentage methane production by 15.8% and 6.1% when added to straw, respectively. Additionally, supplementation of these tannin-containing forages significantly increased (P < 0.05) organic matter digestibility of hay and straw. It was concluded that supplementation of tannin-containing forages could strategically be used to decrease methane emission from rumen fermentation in vitro, and at the same time increase the quality of basal diets. Key words: gas production, digestibility, tannin, methane, forage